Developments in Nanoparticles Enhanced Biofuels and Solar Energy in Malaysian Perspective: A Review of State of the Art - Fayaz H.; Khan S.A.; Saleel C.A.; Shaik S.; Yusuf A.A.; Veza I.; Fattah I.M.R.; Rawi N.F.M.; Asyraf M.R.M.; Alarifi I.M. (Hindawi Limited, 2023)
Biodiesel; Electric power systems; Energy harvesting; Energy policy; Energy utilization; Fossil fuels; Nanoparticles; Nanostructured materials; Solar power generation; 'current; Alternative to fossil fuels; Energy-consumption; Environmental concerns; Malaysia; Malaysians; Oil Prices; Rapid expansion; Renewable energy source; State of the art; Solar energy